Peran Serta Perguruan Tinggi dalam Kepedulian Bencana Erupsi Gunung Semeru Tahun 2021 - Gatut Rubiono; Neni Nur Indah Sari; Edvin Cahyono (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
Mount Semeru, which is located in Malang and Lumajang districts, East Java, is an active volcano with a high frequency of eruptions. This mountain in early December 2021 experienced an eruption that had an impact on the surrounding community in Lumajang district. The academic community of PGRI Banyuwangi University (Uniba) seeks to help the community by raising funds and other assistance. This is done by communicating with related parties so that assistance can be given appropriately, both in terms of form and target. The activity was carried out together with students who took shelter in student organizations. The delivery of assistance is carried out directly in the form of financial assistance to the authorities. This form of assistance is in accordance with the direction of the relevant parties where the logistics in the form of physical needs have been fulfilled.